UKULELE AFFECTIONS AND HAWAIIAN FAMILY CONNECTIONS The Music and Memories of Musician/Producer Rick Cunha. (3rd October 2015) - NEUENFELDT, KARL
Abstract : Extended interview with Rick Cuhuna. Rick Cunha is a multi-instrumentalist musician, producer and songwriter with a long connection to ukulele both personally and professionally. His paternal grandfather was Sonny Cunha, a multi-talented Portuguese- Hawaiian bandleader, politician and entrepreneur as well as composer of classic Hawaiian hapa haole songs such as Hula Blues, Hapa Haole Hula Girl, Honolulu Tomboy and even the Yale University fight song Bula Bula. Sonny also sold ukuleles in Honolulu in the early 1900s, some of which Cunha still uses for recording projects at his Rainbow Garage recording studio in Van Nuys, California.